2021
DOI: 10.3390/pharmaceutics13091346
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Atopic Dermatitis Control with Low-Concentration Propolis-Loaded Cold Cream

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease that is difficult to treat. Traditional cold cream, a water-in-oil emulsion made from beeswax, is used to alleviate AD symptoms in clinical practice, although its effectiveness has not been scientifically proven. The addition of propolis has the potential to impart anti-inflammatory properties to cold cream. However, in high concentrations, propolis can trigger allergic reactions. Thus, the objective of this work was to develop a cold cream formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…When the monocytes were challenged with MAGE-1 or LPS, propolis inhibited the expression of pro-inflammatory TNF-α and IL-6 and up-regulated the anti-inflammatory IL-10 [ 12 ]. Others studies have also confirmed the efficacy of propolis extracts from various geographical locations in reducing the expression of the pro-inflammatory cytokines TNF-α, IL-1β, and IL-6 in macrophage, LPS induced-THP-1,monosodium urate crystals (MSU)-activated THP-1 cells, and LPS-induced human peripheral blood mononuclear cell (PMBC) cell cultures [ 13 , 14 , 16 , 19 , 21 , 22 , 23 , 26 , 28 ].…”
Section: Resultsmentioning
confidence: 95%
“…When the monocytes were challenged with MAGE-1 or LPS, propolis inhibited the expression of pro-inflammatory TNF-α and IL-6 and up-regulated the anti-inflammatory IL-10 [ 12 ]. Others studies have also confirmed the efficacy of propolis extracts from various geographical locations in reducing the expression of the pro-inflammatory cytokines TNF-α, IL-1β, and IL-6 in macrophage, LPS induced-THP-1,monosodium urate crystals (MSU)-activated THP-1 cells, and LPS-induced human peripheral blood mononuclear cell (PMBC) cell cultures [ 13 , 14 , 16 , 19 , 21 , 22 , 23 , 26 , 28 ].…”
Section: Resultsmentioning
confidence: 95%
“…The presence of acacetin flavonoids is responsible for propolis' anti‐inflammatory activities according to (Ramos & Miranda, 2007). Several studies have also shown that artepillin C is one of the bioactive compounds found in propolis that affects inflammatory processes (Cardoso et al, 2022; Kashiwakura et al, 2021; Kitamura et al, 2018; Martin et al, 2021; Mikami et al, 2021).…”
Section: Anti‐inflammatory Properties Of Propolismentioning
confidence: 99%
“…It has been shown that CAPE also promotes wound healing by accelerating wound healing phase to maturation phase [9]. Propolis demonstrates promising potential as a therapeutic agent for wound healing in the context of burns [24] and eczema [30].…”
Section: Antibacterial Activity Of Eep Towards Esbl-producing K Pneum...mentioning
confidence: 99%